The Fed's international dollar liquidity facilities: New evidence on effects - Linda S. Goldberg; Fabiola Ravazzolo (Federal Reserve Bank of New York, 2021)
In March 2020, the Federal Reserve eased the terms on its standing swap lines in collaboration with other central banks, reactivated temporary swap agreements, and then introduced the new Foreign and International Monetary Authorities (FIMA) Repo Facility. We provide new evidence on how the central bank swap lines and FIMA Repo Facility can reduce strains in global dollar funding markets and U.S. Treasury markets during extreme stress events. These facilities are found to reduce strains in dollar funding markets as measured by foreign exchange swap basis spreads or covered interest parity deviations, as well as the sensitivity of these strains to risk sentiment deterioration. Cross-border flows through banks for excess liquidity support purposes are reduced in the near term and the risk sensitivity of equity and bond fund flows declines. However, access to these facilities leaves longer-term patterns of cross-border liquidity and capital flows broadly unchanged. While official sector liquidity hoarding and 'dash for cash' activity are expected to be lower with access to these facilities, initial evidence does not show differential changes in foreign exchange reserve holdings by central banks in relation to liquidity access.
Keywords: F15; F21; F32; F36; G15; 330; dollar; central bank swap lines; credit; liquidity; capital flows; foreign exchange